Sai Baba Temple - Mumbai Archive Project Team (Jio Institute, 2024)
A modern structure, the Sai Baba Temple, built by followers of Shirdi Sai Baba, a fakir (ascetic) who is worshipped by both Hindu and Muslim devotees, is situated close to the Worli Fort. The area around the temple now serves as a space for hosting cultural events at Worli Koliwada.